(1)3x2+6x-4=0(配方法) (2)5x2-2=-x(配方法) (3)y2+2=2
(4)x2-3x-1=0(公式法) (5)(x-2)2-5(2-x)=-6(因式分解法) (6)(x+2)2=2x+4 (因式分解法) |
(1)3x2+6x-4=0,
移项得:3x2+6x=4,
把二次项系数化为1得:3(x2+2x)=4,
配方得:3(x2+2x+1-1)=4,
3(x+1)2-3=4,
3(x+1)2=7,
(x+1)2=
,7 3
两边直接开平方得:x+1=±
,21 3
则x1=-1+
,x2=-1-21 3
;21 3
(2)5x2-2=-x,
移项得:5x2+x=2,
把二次项系数化为1得:5(x2+
x)=2,1 5
x2+
x=1 5 2 5
配方得:x2+
x+(1 5
)2=1 10
+(2 5
)2,1 10
(x+
)2=1 10
,41 100
两边直接开平方得:x+
=±1 10
,41 10
x+
=1 10
,x+41 10
=-1 10
,41 10
解得:x1=
,x2=
-141 10
;-
-141 10
(3)把y2+2=2
y变形为y2-22
y+2=0,2
其中a=1,b=-2
,c=2,2
△=(-2
)2-4×1×2=0,2
∴y1=y2=-
=-b± b2-4ac 2a
;2
(4)x2-3x-1=0,
其中a=1,b=-3,c=-1,
△=(-3)2-4×1×(-1)=13,
x=-
=-b± b2-4ac 2a
,3± 13 2
∴x1=
,x2=3+ 13 2
;3- 13 2
(5))(x-2)2-5(2-x)=-6,
移项得:(x-2)2+5(x-2)+6=0,
分解因式得:(x-2+2)(x-2+3)=0,
x(x+1)=0,
则:x1=0,x2=-1.
(6)(x+2)2=2x+4,
移项得:(x+2)2-(2x+4)=0,
(x+2)2-2(x+2)=0,
分解因式得:(x+2)(x+2-2)=0,
(x+2)x=0,
解得:x1=-2,x2=0.